CONFLICT MANAGEMENT STRATEGIES IN THE SCHOOL ENVIRONMENT AND THEIR IMPACT ON EDUCATIONAL PERFORMANCE - Erwin Erwin; Reina A. Hadikusumo; Amândio de Araújo Sarmento (International Journal of Teaching and Learning, 2025)
Conflict management strategies in the school environment include a range of approaches designed to resolve disputes and promote constructive communication between students, teachers and staff. By applying mediation techniques, negotiation and training in social-emotional skills, schools aim to reduce the incidence of conflict and promote peaceful problem solving. The research method conducted in this study uses the literature research method. The results show that effective conflict management has a significant impact on enhancing positive school climate, student engagement, and improving learning achievement. Schools that successfully integrated proactive and educative conflict management approaches in their curriculum and school policies showed a decrease in conflict incidents, an increase in students' ability to resolve conflict constructively, and better emotional well-being. In addition, this study identifies the critical role of school leadership and the participation of all stakeholders, including teachers, parents and students, in maintaining a school climate conducive to learning and positive conflict resolution.